Odnos prebivalcev obmejnih območij Slovenije do slovensko-hrvaške državne meje - Špes, Metka (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2001)
Article represents basic geographical characteristics of four sample border areas (Slovenska Istra, Bela Krajina, Spodnje Posavje and Spodnje Podravje), which were included in the research about the effects of a new state border on the living of inhabitants. We analysed their comprehension of changes in economic and social conditios, traffic currencies, interethnic relations, etc. Questioned persons (1200 questionnaires) were estimating also development possibilities of domestic region in the light of its border position as well as obstacles for cooperation with the neighbouring Croatia and first of all with its border regions. Also current projects of transborder cooperation are represented.
Keywords: Croatia; državne meje; Hrvatska; obmejna območja; obmejno sodelovanje; prebivalstvo; regionalni razvoj; Slovenia; Slovenija